"I'm Going to Be Straight, Just Like How My Father Would've Wanted": Adolescent Male Sexuality, Shame, and Symptoms of Mental Illness in Adam Silvera's More Happy Than Not and John Corey Whaley's Highly Illogical Behaviour. Issue 1 (1st December 2022) - Salt-Raper, Emma
Abstract: While the increasing visibility of LGBTQ+ identities in recent young adult fiction has received much critical attention, such novels that contain the added complex distinction of adolescent male mental illness and recovery represent an underexamined area. This article produces readings of two recent young adult texts that feature gay male protagonists who experience mental illness: Adam Silvera's More Happy Than Not (2015) and John Corey Whaley's Highly Illogical Behaviour (2016). It investigates how the texts' embedded heteronormative scripts, relationships between the symptoms and the self, and frameworks of health-related shame are fraught with anxieties, producing a complex double movement that simultaneously establishes and undermines gay males' control over their mental illnesses and recovery trajectories to move the characters between spaces of empowerment and marginalization.